Autologous Blood Transfusion for Postpartum Hemorrhage. Issue 5 (September 2017) - Greenawalt, Julia A.; Zernell, Denise
Abstract : Abstract: Postpartum hemorrhage (PPH) is a leading contributor to maternal morbidity and mortality in the United States and globally. Although the rate of PPH is generally decreasing nationally, severity of PPH appears to be increasing, potentially related to the various comorbidities associated with women of childbearing age. There is increasing evidence of risks associated with allogeneic blood transfusion, which has historically been the classic therapeutic approach for treatment to PPH. Pregnant women are particularly susceptible to the implications of sensitization to red cell antigens, a common sequela to allogenic blood transfusion. Autologous blood transfusion eliminates the potential of communicable disease transmission as well as the conceivable threat of a blood transfusion reaction. Recent technological advances allow cell salvage coupled with the use of a leukocyte filter to be used as an alternative approach for improving the outcome for women experiencing a PPH. Modest changes in standard operating procedure and continued training in use and application of cell salvaged blood may assist in minimizing negative outcomes from PPH. Salvaged blood has been demonstrated to be at least equal and often superior to banked blood. We discuss nursing implications for application of this technology for women with PPH. Continued research is warranted to evaluate the impact that application of cell salvage with filtration has on the patient experiencing a PPH. Abstract : Autologous blood transfusion is an option for postpartum hemorrhage. An overview of the rationale, process, equipment, and clinical implications for nurses is provided.